Social and emotional learning in a preschool context:|A teacher-led intervention program - Küçüközdemir, Özlem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Preschool teachers play a crucial role in the social and emotional development of young children. They educate a large number of students throughout their career; thus, training the teachers can be considered as a cost- and time-effective method for improving children’s social and emotional learning (SEL). This study aimed to train preschool teachers to implement an evidence-based social and emotional skills program and to examine the program’s effectiveness on children’s development. Four preschools were randomly assigned to experimental and control groups. Pre- and post-test evaluation was conducted with 61 children in six control classes and 85 children in seven intervention classes. All participants were between the ages of 4-6 years. Emotion comprehension and social problem-solving skills of children were assessed individually with standardized tests. Data on social competence of children was obtained by parent and teacher ratings. The intervention program included six bi-weekly teacher training sessions and weekly in-class coaching in the experimental group classes for 12 weeks. The results indicated that the intervention was effective in improving emotion comprehension and social problem-solving skills based on child report. However, parents and teachers did not observe significant differences in children’s social competence levels and behavioral outcomes.
Keywords: Child development.; Emotional problems of children.; Preschool teachers.